Acquired T790M Mutation in Patients Failing Treatment with First or Second-Generation EGFR-Tyrosine Kinase Inhibitors - Chai, Chee Shee; Liam, Chong Kin; Poh, Mau Ern; Ong, D. B. L.; Cheah, P. L.; Pang, Yong Kek; Ho, G. F.; Alip, A. (Elsevier, 2019)
Background: The majority of patients with epidermal growth factor receptor (EGFR)-mutant advanced non-small cell lung cancer (NSCLC) develop resistance to first- or second-generation EGFR-tyrosine kinase inhibitor (TKI) after a median treatment period of 12 months. This study aimed to determine the prevalence and predictors of acquired T790M mutation as a resistance mechanism among these patients.